2015
DOI: 10.1039/c5fd00074b
|View full text |Cite
|
Sign up to set email alerts
|

Coupling single quantum dots to plasmonic nanocones: optical properties

Abstract: Coupling a single quantum emitter, such as a fluorescent molecule or a quantum dot (QD), to a plasmonic nanostructure is an important issue in nano-optics and nano-spectroscopy, relevant for a wide range of applications, including tip-enhanced near-field optical microscopy, plasmon enhanced molecular sensing and spectroscopy, and nanophotonic amplifiers or nanolasers, to mention only a few. While the field enhancement of a sharp nanoantenna increasing the excitation rate of a very closely positioned single mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…4. Due to the modification of the local density of optical states by the plasmon resonance and the antenna properties of the plasmonic nanostructures, the fluorescence in the hybrid system appears to be increased [4,5,7,37,38]. For the wires with 63 and 74 nm widths, the left shoulder of the broad fluorescence curve of DIP at around 630 nm is most strongly enhanced (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…4. Due to the modification of the local density of optical states by the plasmon resonance and the antenna properties of the plasmonic nanostructures, the fluorescence in the hybrid system appears to be increased [4,5,7,37,38]. For the wires with 63 and 74 nm widths, the left shoulder of the broad fluorescence curve of DIP at around 630 nm is most strongly enhanced (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Several mechanisms can lead to the fluorescence enhancement in the hybrid system: the increase of light absorption by the DIP molecules due to the enhanced near-field at the surface of the plasmonic nanostructures, changes of the radiative and non-radiative transition rates induced by the metal nanostructures, and/or the coupling of the nanostructures' near-field to the far-field [6,7,37,38]. Because of the unpolarized excitation in the fluorescence setup, a potential absorption effect should be visible in both the TE-and TM-polarized emission data (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of these intriguing characteristics, CVBs are used as novel probes for imaging the orientation of molecules or nanostructures. 29 33 Owing to the tensorial character of nonlinear interactions, CVBs are also used to improve the orientation sensitivity of nonlinear microscopy techniques. 34 39 In the context of oligomer studies, focused CVBs have been shown to excite collective dark modes (with zero net dipole moment), which cannot be accessed using linear polarization under normal incidence.…”
mentioning
confidence: 99%